Prognosis of preinvasive dlsease of the cervix in HIV infected women: evidence from the literature and dlscussion of it’s treatment effectiveness - Russomano, Fábio B.; Camargo, Maria José; Freire, Rafael; Reis, Aldo F.F.; Grinsztejn, Beatriz (Brazilian Journal of Sexually Transmitted Diseases, 2003)
HIV is infecting progressively more women. With the better management of HIV+ women and with the possibility of using highly active antiretroviral the- rapy (HAART), chronic diseases, as pre invasive cervical lesions, had become relevant. Many evidences show that these lesions tend to be more prevalent, incident and recurrent after conventional therapy in HIV+ women. The assessment of lhe medicai literature that leads with the prognosis of these lesions after conventional therapy shows it’s limitation. The information extracted from the papers with lesser risk of bias points that the probability of progression from low grade intraepithelial lesions (LSIL) to high grade intraepithelial lesions (HSIL) in HIV+ women is near 55% and of regression of LSIL is 25%; that the probability of recurrence of HSIL after conventional therapy may be between 56.2% and 60%, or 30.4/1,000 patient-month, with relative risk of 4-5.4; that are possible prognostic factors: grade of cervical lesion treated, margin involvement, immunodeficiency measured by CD4+ count, HIV virai load and use of HAART. Although these evidences, there aren’t studies with total applicability to our patienls. The high recurrence risk of cervical pre invasive diseases leads to a discussion of the effectiveness of conventional therapies in HIV+ women. However, a careful follow-up of these women in order to detect and treat recurrent lesions can be an effective strategy.